2017
DOI: 10.21873/anticanres.12133
|View full text |Cite
|
Sign up to set email alerts
|

Cold Atmospheric Plasma (CAP) and CAP-Stimulated Cell Culture Media Suppress Ovarian Cancer Cell Growth – A Putative Treatment Option in Ovarian Cancer Therapy

Abstract: In summary, the CAP application in oncological surgery leads to strong anti-proliferative effects and opens up novel opportunities for the OC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Against this background, CAP treatment can be considered a new alternative in anti-oncological therapy. It has been shown that CAP treatment can inhibit both the proliferation and the cell mobility of in vitro propagated tumor cells [ 35 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Against this background, CAP treatment can be considered a new alternative in anti-oncological therapy. It has been shown that CAP treatment can inhibit both the proliferation and the cell mobility of in vitro propagated tumor cells [ 35 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that oxidative stress triggers apoptosis in epithelial cells [ 69 ]. Although CAP-induced apoptosis has been demonstrated in various tumor entities [ 34 , 35 , 70 , 71 ], the effect in endothelial cells is still largely unexplored. Analysis of apoptotic processes revealed both increased DNA fragmentation and increased activity of caspase 3 and caspase 7 in HDMEC directly treated with CAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the potential of CAP in the treatment of gynaecological oncologic diseases can be illustrated by the example of current studies evaluating, for example, breast [55] or ovarian cancer [73]. There have not been any large clinical studies on CAP in gynaecological malignancies, however, although VSCC or cervical lesions are suitable for its use at large scale [69].…”
Section: Current Knowledge Of In Vitro Cell Lines and Further Potentimentioning
confidence: 99%
“…Cold atmospheric plasma (CAP) treatments have offered very promising opportunities for wound healing and antiseptics. Moreover, CAP indicated promising anti-neoplastic effects on several tumor entities, e.g., melanoma, glioma, pancreatic, and several gynecological tumors, particularly breast cancer, ovarian cancer, and cervical cancer [2][3][4][5][6][7][8][9][10][11][12][13]. CAP treatment led to sufficient inhibition of cancer cell growth, interestingly, without tissue swelling, inflammation, or pain.…”
Section: Introductionmentioning
confidence: 99%